Picazo Zappino, Julia (2017). El suicidio actual [Current suicide]. Madrid: Editorial EOS. 256 pp. ISBN-13: 978-8497277013 - Castillo Patton, Andy Eric (Cuadernos de Trabajo Social, 2021)
Reseña de la obra de Picazo Zappino, Julia (2017). El suicidio actual [Current suicide]. Madrid: Editorial EOS. 256 pp. ISBN-13: 978-8497277013